Secondary battery and electronic device
By using silicon carbon particles of different particle sizes and regulating electrolyte components in secondary batteries, the problems of capacity attenuation and safety hazards in the later cycle of high-energy-density secondary batteries are solved, and more stable energy release and safety performance are achieved.
Patent Information
- Application Number
- CN202411827605.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-12
AI Technical Summary
High-energy density secondary batteries are prone to capacity attenuation and thermal runaway after long-term circulation, resulting in safety hazards and reduced discharge rate, making it difficult to play a stable battery life advantage in the long term.
By using silicon carbon particles of different particle sizes in the negative electrode material layer of the secondary battery and controlling their roundness, combined with the use of diethyl carbonate and ethyl propionate in the electrolyte of a specific proportion, the silicon carbon particles are optimized. Distribution and formation of electrolyte interface film improve the conductivity and stress buffering ability of the negative electrode material.
It achieves the improvement of safety performance, discharge rate and capacity retention capabilities in the later stage of the secondary battery cycle while high energy density, reduces the risk of powdering, and extends the battery life.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application belongs to the field of energy storage technology, and specifically relates to a secondary battery and an electronic device. Background Art
[0002] Secondary batteries can store and release energy during the charge and discharge process through electrochemical reactions, and can be recycled thousands of times. With their excellent energy efficiency and economy, secondary batteries are widely used in portable electronic devices, electric vehicles, energy storage systems and other fields. Among them, secondary batteries with high energy density have a relatively longer battery life, which is beneficial to improve the performance of application equipment. However, after long-term cyclic use, secondary batteries with high energy density are prone to capacity attenuation and diving, which is not conducive to the long-term and stable use of their battery life advantages, and are also prone to safety problems such as thermal runaway, creating safety hazards. Therefore, how to improve the capacity retention ability and safety performance of high energy density secondary batteries in the later stages of the cycle is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0003] The purpose of the present application is to provide a secondary battery and an electronic device, which can achieve a higher energy density while improving the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle.
[0004] In the first aspect, the present application provides a secondary battery. The secondary battery comprises a positive electrode, a negative electrode and an electrolyte, the negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer comprises silicon carbon particles, and the particle size of the silicon carbon particles is D µm. The silicon carbon particles comprise first silicon carbon particles and second silicon carbon particles; when 5≤D≤13, the silicon carbon particles are first silicon carbon particles, and the circularity of the first silicon carbon particles is R1, when 0.1≤D≤2, the silicon carbon particles are second silicon carbon particles, and the circularity of the second silicon carbon particles is R2, and the negative electrode material layer satisfies: R1 / R2>1; the electrolyte comprises diethyl carbonate and ethyl propionate, and based on the mass of the electrolyte, the mass percentage of diethyl carbonate is S1%, and the mass percentage of ethyl propionate is S2%, and 2.3≤S2 / S1≤6. The secondary battery provided in the present application achieves a higher energy density while taking into account the improvement of the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later stage of the cycle.
[0005] Without being limited to any theory, the inventors of the present application have found that although the compaction density of the negative electrode sheet can be further improved by mixing large-particle silicon-carbon particles and small-particle silicon-carbon particles, thereby improving the energy density of the secondary battery, the expansion and contraction degree of silicon-carbon particles of different particle sizes during the charge and discharge cycle is different. After multiple cycles, the negative electrode material is affected by uneven stress and accelerates pulverization. And compared with large-particle silicon-carbon particles, small-particle silicon-carbon particles are more likely to produce high stress points locally, and the risk and degree of pulverization are higher, which also leads to the fact that the pulverization inside the negative electrode material layer is usually uneven. The above problems lead to an increase in the safety risk of secondary batteries in the later stage of the cycle, a decrease in the discharge rate and an increase in the capacity loss rate. The present application satisfies the above relationship by regulating the roundness of the first silicon-carbon particles and the second silicon-carbon particles, which can achieve a higher energy density while taking into account the improvement of the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle. Furthermore, by making the electrolyte contain both diethyl carbonate and ethyl propionate and adjusting the value of S2 / S1 to satisfy: 2.3≤S2 / S1≤6, the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle can be further improved.
[0006] The inventor speculates that the first silicon-carbon particles have a particle size of 5µm to 13µm, which can act as a compressive skeleton in the negative electrode material layer. Making the first silicon-carbon particles more circular can buffer the stress caused by the volume change of the silicon-carbon particles to a greater extent, and reduce the probability of the second silicon-carbon particles being pulverized due to local high stress. In addition, when the first silicon-carbon particles with high circularity are accumulated in the negative electrode material layer, larger pores will be formed. The second silicon-carbon particles have a particle size of 0.1µm to 2µm, which can be fully filled in the above-mentioned pores to provide a conductive path for the negative electrode material. When the second silicon-carbon particles with lower circularity are filled in the above-mentioned pores, more contact points and increased contact area can be formed with the surrounding materials, providing a rich conductive network for the negative electrode material layer, and compensating for the problem that the pores of the negative electrode material layer are larger and the conductive path is insufficient when the first silicon-carbon particles with high circularity are accumulated in the electrode. In addition, due to the large difference in the particle size of the two silicon-carbon particles, the electrolyte difference that is conducive to the formation of a suitable solid electrolyte interface film (SEI film) by the two silicon-carbon particles is large. For example, small-sized silicon-carbon particles have a higher specific surface area and a higher reaction activity with the electrolyte, so they consume a lot of electrolyte and are more likely to form an SEI film that is too thick. Large-sized silicon-carbon particles have a lower specific surface area and are more likely to form an SEI film that is too thin. By adjusting the relationship between the mass percentages of diethyl carbonate and ethyl propionate, the needs of the two types of silicon-carbon particles for electrolyte components can be taken into account. In summary, by making the negative electrode and electrolyte of the secondary battery meet the above settings, it is possible to achieve a higher energy density while comprehensively improving the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle.
[0007] In some embodiments, 0.05≤R1-R2≤0.15. By adjusting the value of R1-R2 within the above range, the safety performance, discharge rate and capacity retention ability of the secondary battery in the later cycle can be further improved.
[0008] In some embodiments, the first silicon-carbon particles contain silicon and carbon, and the mass proportion of silicon is C1%, 35≤C1≤55, based on the mass sum of the silicon and carbon elements of the first silicon-carbon particles; and / or, the second silicon-carbon particles contain silicon and carbon, and the mass proportion of silicon is C2%, 45≤C2≤65, based on the mass sum of the silicon and carbon elements of the second silicon-carbon particles. By adjusting the values of C1 and / or C2 within the above range, the expansion degree of the first silicon-carbon particles and / or the second silicon-carbon particles can be regulated, thereby improving the safety performance, discharge rate and capacity retention ability of the secondary battery in the later cycle.
[0009] In some embodiments, 1.2≤C2 / C1≤1.7. By adjusting the value of C2 / C1 within the above range, the expansion degree of the first silicon-carbon particles and the second silicon-carbon particles can be coordinated, and the safety performance, discharge rate and capacity retention ability of the secondary battery in the later cycle can be further improved.
[0010] In some embodiments, the silicon-carbon particles include third silicon-carbon particles; when 2<D<5, the silicon-carbon particles are third silicon-carbon particles; the number of the first silicon-carbon particles is N1, the number of the second silicon-carbon particles is N2, the number of the third silicon-carbon particles is N3, and N3 / (N1+N2+N3)<0.2. Adjusting the value of N3 / (N1+N2+N3) within the above range can improve the safety performance, discharge rate and capacity retention ability of the secondary battery in the later cycle.
[0011] In some embodiments, 2.8≤S2 / S1≤4.5. By adjusting the value of S2 / S1 within the above range, the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle can be further improved.
[0012] In some embodiments, the electrolyte contains fluoroethylene carbonate and vinylene carbonate, and based on the mass of the electrolyte, the mass percentage of fluoroethylene carbonate is A1%, the mass percentage of vinylene carbonate is A2%, and 0.5≤A1 / (100×A2)≤1.8. By making the electrolyte contain both fluoroethylene carbonate and vinylene carbonate and adjusting the value of A1 / (100×A2) within the above range, the electrical conductivity between the first silicon-carbon particles and the second silicon-carbon particles can be improved, thereby further improving the safety performance, discharge rate and capacity retention of the secondary battery in the later stage of the cycle.
[0013] In some embodiments, 0.7≤A1 / (100×A2)≤1.5. By adjusting the value of A1 / (100×A2) within the above range, the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle period can be further improved.
[0014] In some embodiments, 0.90≤R1≤0.98. By adjusting the value of R1 within the above range, the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle can be further improved.
[0015] In some embodiments, 0.78≤R2≤0.92. By adjusting the value of R2 within the above range, the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle can be further improved.
[0016] In some embodiments, 5≤S1≤20. By adjusting the value of S1 within the above range, the safety performance, discharge rate and capacity retention capability of the secondary battery in the later cycle can be further improved.
[0017] In some embodiments, 20≤S2≤45. By adjusting the value of S2 within the above range, the safety performance, discharge rate and capacity retention capability of the secondary battery in the later cycle can be further improved.
[0018] In some embodiments, 11≤A1≤18. By adjusting the value of A1 within the above range, the safety performance, discharge rate and capacity retention capability of the secondary battery in the later cycle period can be further improved.
[0019] In some embodiments, 0.05≤A2≤0.5. By adjusting the value of A2 within the above range, the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle can be further improved.
[0020] In some embodiments, the electrolyte contains tetramethyltetravinylcyclotetrasiloxane, and the mass percentage of tetramethyltetravinylcyclotetrasiloxane is 0.01% to 0.1% based on the mass of the electrolyte. The electrolyte includes tetramethyltetravinylcyclotetrasiloxane and the mass percentage of tetramethyltetravinylcyclotetrasiloxane is adjusted within the above range to improve the conductivity of the SEI film on the surface of the second silicon-carbon particles, and improve the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle.
[0021] In some embodiments, the electrolyte contains diethyl (cyanomethyl) phosphonate, and the mass percentage of diethyl (cyanomethyl) phosphonate is 0.1% to 0.8% based on the mass of the electrolyte. The electrolyte contains diethyl (cyanomethyl) phosphonate and the mass percentage of diethyl (cyanomethyl) phosphonate is adjusted to be within the above range, which can improve the elasticity of the SEI film on the surface of the first silicon-carbon particles and improve the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle.
[0022] In some embodiments, the elongation of the negative electrode current collector is δ%, and 3≤δ≤8. By adjusting the elongation of the negative electrode current collector within the above range, the possibility of the first silicon-carbon particles and the second silicon-carbon particles generating uneven stress on the negative electrode current collector and causing the current collector to deform can be reduced, thereby improving the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle.
[0023] In some embodiments, the average particle size of the first silicon-carbon particles is RA μm, and 1.3≤RA / δ≤3.6. By adjusting the value of RA / δ within the above range, the relationship between the stress applied to the current collector when the first silicon-carbon particles expand and the expandable space provided to the negative electrode material layer by the elongation of the current collector can be balanced, thereby improving the safety performance, discharge rate and capacity retention of the secondary battery in the later stage of the cycle.
[0024] In some embodiments, the silicon-carbon particles include a carbon carrier and silicon crystals at least partially distributed inside the carbon carrier. This arrangement can improve the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle.
[0025] In a second aspect, the present application provides an electronic device, which includes the secondary battery provided in the first aspect of the present application. The electronic device provided in the second aspect of the present application achieves a higher energy density while further improving the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle.
[0026] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. DETAILED DESCRIPTION
[0027] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0028] Unless expressly stated otherwise, the following terms used in this application have the meanings indicated below.
[0029] In the first aspect, the present application provides a secondary battery. The secondary battery comprises a positive electrode, a negative electrode and an electrolyte, the negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, the negative electrode material layer comprises silicon-carbon particles, and the particle size of the silicon-carbon particles is D µm. The silicon-carbon particles comprise first silicon-carbon particles and second silicon-carbon particles; when 5≤D≤13, the silicon-carbon particles are first silicon-carbon particles, and the circularity of the first silicon-carbon particles is R1, when 0.1≤D≤2, the silicon-carbon particles are second silicon-carbon particles, and the circularity of the second silicon-carbon particles is R2, and the negative electrode material layer satisfies: R1 / R2>1. The secondary battery provided in the present application achieves a higher energy density while taking into account the improvement of the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later stage of the cycle.
[0030] negative electrode The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent the active material (e.g., lithium metal) from being accidentally precipitated on the negative electrode during charging.
[0031] The negative electrode active material includes silicon carbon particles. In some embodiments, the negative electrode material layer satisfies: R1 / R2>1. In some embodiments, 1.02≤R1 / R2≤1.23. In some embodiments, 1.02≤R1 / R2≤1.18. In some embodiments, 1.06≤R1 / R2≤1.23. In some embodiments, 1.02≤R1 / R2≤1.15. In some embodiments, 1.06≤R1 / R2≤1.18. In some embodiments, 1.15≤R1 / R2≤1.23. In some embodiments, 1.02≤R1 / R2≤1.06. In some embodiments, 1.06≤R1 / R2≤1.15. In some embodiments, 1.15≤R1 / R2≤1.18. In some embodiments, 1.18≤R1 / R2≤1.23. In some embodiments, the value of R1 / R2 is 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23 or a value within the range of any two thereof. By adjusting the value of R1 / R2 within the above range, the stacking relationship of the first silicon-carbon particles and the second silicon-carbon particles in the negative electrode material layer can be regulated, stress can be reduced, and more conductive paths can be provided, thereby further improving the safety performance, discharge rate, and capacity retention of the secondary battery in the later cycle.
[0032] In some embodiments, 0.05≤R1-R2≤0.15. In some embodiments, 0.05≤R1-R2≤0.13. In some embodiments, 0.13≤R1-R2≤0.15. In some embodiments, the value of R1-R2 is 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15 or a value within the range of any two thereof. By adjusting the value of R1-R2 within the above range, the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle can be further improved.
[0033] In some embodiments, 0.90≤R1≤0.98. In some embodiments, 0.90≤R1≤0.96. In some embodiments, 0.92≤R1≤0.98. In some embodiments, 0.90≤R1≤0.94. In some embodiments, 0.92≤R1≤0.96. In some embodiments, 0.94≤R1≤0.98. In some embodiments, 0.90≤R1≤0.92. In some embodiments, 0.92≤R1≤0.94. In some embodiments, 0.94≤R1≤0.96. In some embodiments, 0.96≤R1≤0.98. In some embodiments, the value of R1 is 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98 or a value within the range of any two thereof. By adjusting the value of R1 within the above range, the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later stage of the cycle can be further improved.
[0034] In some embodiments, 0.78≤R2≤0.92. In some embodiments, 0.78≤R2≤0.85. In some embodiments, 0.83≤R2≤0.92. In some embodiments, 0.78≤R2≤0.83. In some embodiments, 0.83≤R2≤0.85. In some embodiments, 0.85≤R2≤0.92. In some embodiments, the value of R2 is 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92 or a value within the range of any two thereof. By adjusting the value of R2 within the above range, the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle can be further improved.
[0035] In some embodiments, the first silicon-carbon particles contain silicon and carbon, and based on the mass sum of the silicon and carbon elements of the first silicon-carbon particles, the mass proportion of silicon is C1%, 35≤C1≤55. In some embodiments, 35≤C1≤38. In some embodiments, 38≤C1≤55. In some embodiments, the value of C1 is 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 or a value in the range of any two thereof. Adjusting the value of C1 within the above range can further improve the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle.
[0036] In some embodiments, the second silicon-carbon particles contain silicon and carbon, and based on the mass sum of the silicon and carbon elements of the second silicon-carbon particles, the mass proportion of silicon is C2%, 45≤C2≤65. In some embodiments, 45≤C2≤63. In some embodiments, 48≤C2≤65. In some embodiments, 45≤C2≤48. In some embodiments, 48≤C2≤63. In some embodiments, 63≤C2≤65. In some embodiments, the value of C2 is 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65 or a value in the range of any two thereof. Adjusting the value of C2 within the above range can further improve the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle.
[0037] In some embodiments, 1.2≤C2 / C1≤1.7. In some embodiments, the value of C2 / C1 is 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or a value in the range of any two thereof. By adjusting the value of C2 / C1 within the above range, the safety performance, discharge rate and capacity retention ability of the secondary battery in the later cycle can be further improved.
[0038] In some embodiments, the silicon-carbon particles include third silicon-carbon particles; when 2<D<5, the silicon-carbon particles are third silicon-carbon particles; the number of the first silicon-carbon particles is N1, the number of the second silicon-carbon particles is N2, the number of the third silicon-carbon particles is N3, and N3 / (N1+N2+N3)<0.2. 0.01≤N3 / (N1+N2+N3)≤0.19. In some embodiments, the value of N3 / (N1+N2+N3) is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19 or a value in the range consisting of any two of them. Adjusting the value of N3 / (N1+N2+N3) within the above range can improve the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle.
[0039] In some embodiments, the silicon-carbon particles include a carbon carrier and silicon crystals at least partially distributed inside the carbon carrier. Through this arrangement, the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle period can be improved.
[0040] In some embodiments, the surface of the silicon-carbon particles may include functional materials such as polymers, conductive agents, solid electrolytes, etc., separately or simultaneously, to further improve the performance of the secondary battery.
[0041] In some embodiments, the surface of the silicon-carbon particles may include a carbon layer, and the thickness of the carbon layer is preferably 10 to 100 nanometers. The carbon layer may be disposed on most of the surface of the silicon-carbon particles, and more preferably disposed on the entire surface of the silicon-carbon particles. By providing a carbon layer on the surface of the silicon-carbon particles, it is beneficial to reduce the gas production of the silicon-carbon particles during the preparation of the secondary battery, improve the flatness of the negative electrode sheet, and thus improve the performance of the secondary battery.
[0042] Optionally, the negative electrode material layer may further include crystalline carbon material and / or amorphous carbon material. The crystalline carbon material may be natural graphite, artificial graphite, etc., and the amorphous carbon may be soft carbon (low-temperature calcined carbon), hard carbon, intermediate phase pitch carbide or calcined coke, etc.
[0043] In some embodiments, the negative electrode material layer includes a conductive agent; the type of the conductive agent is not limited, and any known conductive material can be used. Examples of the conductive agent may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above conductive agents may be used alone or in any combination.
[0044] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode material layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.
[0045] In some embodiments, the elongation of the negative electrode current collector is δ%, 3≤δ≤8. In some embodiments, 3≤δ≤6. In some embodiments, 4≤δ≤8. In some embodiments, 3≤δ≤4. In some embodiments, 4≤δ≤6. In some embodiments, 6≤δ≤8. In some embodiments, the elongation of the negative electrode current collector is a value within the range of 3, 4, 5, 6, 7, 8 or any two thereof. By adjusting the elongation of the negative electrode current collector within the above range, the possibility of the first silicon-carbon particles and the second silicon-carbon particles generating uneven stress on the negative electrode current collector and causing deformation of the current collector can be reduced, thereby improving the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle.
[0046] In some embodiments, the average particle size of the first silicon-carbon particles is RA μm, 1.3≤RA / δ≤3.6. In some embodiments, 1.3≤RA / δ≤2.9. In some embodiments, 2.2≤RA / δ≤3.6. In some embodiments, 1.3≤RA / δ≤2.2. In some embodiments, 2.2≤RA / δ≤2.9. In some embodiments, 2.9≤RA / δ≤3.6. In some embodiments, the value of RA / δ is 1.3, 1.4, 1.6, 1.7, 1.9, 2.0, 2.1, 2.2, 2.3, 2.5, 2.6, 2.7, 2.9, 2.9, 3.1, 3.2, 3.3, 3.4, 3.6 or a value in the range of any two thereof. By adjusting the value of RA / δ within the above range, the relationship between the stress applied to the current collector when the first silicon-carbon particles expand and the expandable space provided to the negative electrode material layer by the elongation of the current collector can be balanced, thereby improving the safety performance, discharge rate and capacity retention ability of the secondary battery in the later cycle.
[0047] In some embodiments, 7.9≤RA≤10.7. In some embodiments, 7.9≤RA≤8.6. In some embodiments, 8.6≤RA≤10.7. In some embodiments, the value of RA is 7.9, 8.1, 8.3, 8.4, 8.6, 8.7, 8.9, 9.0, 9.2, 9.3, 9.4, 9.6, 9.7, 9.8, 10.0, 10.1, 10.3, 10.5, 10.7 or a value within the range of any two thereof. Regulating the value of RA to conform to the above range can further improve the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle.
[0048] The negative electrode material layer may further include a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the electrolyte or electrode manufacturing. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, hydroxyethylcarboxymethylcellulose (HECMC) or its salt, carboxymethylcellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyacrylate, polyvinyl alcohol, and the like.
[0049] Exemplarily, the negative electrode can be prepared by the following method: a negative electrode mixture slurry containing a negative electrode binder, silicon-carbon composite particles, a conductive agent, etc. is coated on a negative electrode current collector, and after drying, the negative electrode material layer is formed on both sides of the negative electrode current collector by rolling, thereby obtaining a negative electrode.
[0050] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85 g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.
[0051] Electrolyte The electrolytic solution used in the secondary battery of the present application includes an electrolyte and a solvent that dissolves the electrolyte.
[0052] In some embodiments, the electrolyte comprises diethyl carbonate and ethyl propionate, and based on the mass of the electrolyte, the mass percentage of diethyl carbonate is S1%, the mass percentage of ethyl propionate is S2%, and 2.3≤S2 / S1≤6. In some embodiments, 2.3≤S2 / S1≤4.5. In some embodiments, 2.8≤S2 / S1≤6. In some preferred embodiments, 2.8≤S2 / S1≤4.5. In some embodiments, 4≤S2 / S1≤6. In some embodiments, 2.3≤S2 / S1≤2.8. In some embodiments, 2.8≤S2 / S1≤4. In some embodiments, 4≤S2 / S1≤4.5. In some embodiments, 4.5≤S2 / S1≤6. In some embodiments, the value of S2 / S1 is 2.3, 2.5, 2.6, 2.9, 3, 3.2, 3.4, 3.6, 3.8, 3.9, 4.1, 4.3, 4.6, 4.7, 4.9, 5.1, 5.4, 5.4, 5.7, 6 or a value in the range of any two thereof. By making the electrolyte contain diethyl carbonate and ethyl propionate at the same time and adjusting the value of S2 / S1 within the above range, the film thickness of the solid electrolyte interface film (SEI film) on the surface of the first silicon-carbon particle and the surface of the second silicon-carbon particle can be coordinated, and the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle can be further improved.
[0053] In some embodiments, 5≤S1≤20. In some embodiments, 5≤S1≤15. In some embodiments, 6≤S1≤20. In some embodiments, 5≤S1≤10. In some embodiments, 6≤S1≤15. In some embodiments, 10≤S1≤20. In some embodiments, 5≤S1≤6. In some embodiments, 6≤S1≤10. In some embodiments, 10≤S1≤15. In some embodiments, 15≤S1≤20. In some embodiments, the value of S1 is 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a value within the range of any two thereof. By adjusting the value of S1 within the above range, the safety performance, discharge rate and capacity retention ability of the secondary battery in the later cycle can be further improved.
[0054] In some embodiments, 20≤S2≤45. In some embodiments, 20≤S2≤42. In some embodiments, 35≤S2≤45. In some embodiments, 20≤S2≤40. In some embodiments, 35≤S2≤42. In some embodiments, 40≤S2≤45. In some embodiments, 20≤S2≤35. In some embodiments, 35≤S2≤40. In some embodiments, 40≤S2≤42. In some embodiments, 42≤S2≤45. In some embodiments, the value of S2 is 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45 or a value within the range of any two thereof. By adjusting the value of S2 within the above range, the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle can be further improved.
[0055] In some embodiments, the electrolyte comprises fluoroethylene carbonate and vinylene carbonate, and based on the mass of the electrolyte, the mass percentage of fluoroethylene carbonate is A1%, the mass percentage of vinylene carbonate is A2%, and 0.5≤A1 / (100×A2)≤1.8. In some embodiments, 0.5≤A1 / (100×A2)≤1.5. In some embodiments, 0.7≤A1 / (100×A2)≤1.8. In some embodiments, 0.5≤A1 / (100×A2)≤1.2. In some preferred embodiments, 0.7≤A1 / (100×A2)≤1.5. In some embodiments, 1.2≤A1 / (100×A2)≤1.8. In some embodiments, 0.5≤A1 / (100×A2)≤0.7. In some embodiments, 0.7≤A1 / (100×A2)≤1.2. In some embodiments, 1.2≤A1 / (100×A2)≤1.5. In some embodiments, 1.5≤A1 / (100×A2)≤1.8. In some embodiments, the value of A1 / (100×A2) is 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8 or a value in the range of any two thereof. By making the electrolyte contain both fluoroethylene carbonate and vinylene carbonate and adjusting the value of A1 / (100×A2) within the above range, the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle can be further improved.
[0056] In some embodiments, 11≤A1≤18. In some embodiments, 11≤A1≤15. In some embodiments, 12≤A1≤18. In some embodiments, 11≤A1≤14. In some embodiments, 12≤A1≤15. In some embodiments, 14≤A1≤18. In some embodiments, 11≤A1≤12. In some embodiments, 12≤A1≤14. In some embodiments, 14≤A1≤15. In some embodiments, 15≤A1≤18. In some embodiments, the value of A1 is a value in the range of 11, 12, 13, 14, 15, 16, 17, 18 or any two thereof. By adjusting the value of A1 within the above range, the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle can be further improved.
[0057] In some embodiments, 0.05≤A2≤0.5. In some embodiments, 0.05≤A2≤0.3. In some embodiments, 0.1≤A2≤0.5. In some embodiments, 0.05≤A2≤0.2. In some embodiments, 0.1≤A2≤0.3. In some embodiments, 0.2≤A2≤0.5. In some embodiments, 0.05≤A2≤0.1. In some embodiments, 0.1≤A2≤0.2. In some embodiments, 0.2≤A2≤0.3. In some embodiments, 0.3≤A2≤0.5. In some embodiments, the value of A2 is a value within a range of 0.05, 0.1, 0.2, 0.3, 0.4, 0.5 or any two thereof. By adjusting the value of A2 within the above range, the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later stage of the cycle can be further improved.
[0058] In some embodiments, the electrolyte contains tetramethyltetravinylcyclotetrasiloxane, and the mass percentage of tetramethyltetravinylcyclotetrasiloxane is 0.01% to 0.1% based on the mass of the electrolyte. Exemplarily, the mass percentage of tetramethyltetravinylcyclotetrasiloxane is 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% or a value within the range composed of any two of them. The electrolyte includes tetramethyltetravinylcyclotetrasiloxane and the mass percentage of tetramethyltetravinylcyclotetrasiloxane is adjusted within the above range, which can improve the conductivity of the SEI film on the surface of the second silicon-carbon particles and improve the safety performance, discharge rate and capacity retention ability of the secondary battery in the later cycle.
[0059] In some embodiments, the electrolyte contains diethyl (cyanomethyl) phosphonate, and the mass percentage of diethyl (cyanomethyl) phosphonate is 0.1% to 0.8% based on the mass of the electrolyte. Exemplarily, the mass percentage of diethyl (cyanomethyl) phosphonate is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or a value in the range composed of any two thereof. The electrolyte contains diethyl (cyanomethyl) phosphonate and the mass percentage of diethyl (cyanomethyl) phosphonate is adjusted to be within the above range, which can improve the elasticity of the SEI film on the surface of the first silicon-carbon particles and improve the safety performance, discharge rate and capacity retention ability of the secondary battery in the later cycle.
[0060] The present application has no particular restrictions on the types of other components of the electrolyte, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to dimethyl carbonate, ethylene carbonate, propylene carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethyl methyl carbonate, butylene carbonate, ethylene ethylene carbonate, methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, propyl propionate, γ-butyrolactone, decanoic acid, valerolactone or caprolactone, ethyl At least one of glycol dimethyl ether, dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0061] In some embodiments, the electrolyte is not particularly limited, and any substance known as an electrolyte can be used. The weight of the electrolyte is not particularly limited as long as the effects of the present application are not impaired.
[0062] positive electrode The positive electrode includes a positive electrode collector and a positive electrode material layer disposed on a surface of the positive electrode collector.
[0063] The positive electrode material layer contains positive electrode active material, and the positive electrode material layer can be one layer or multiple layers. Each layer of the multiple layers of positive electrode active material can contain the same or different positive electrode active materials. The positive electrode active material is any material that can reversibly embed and de-embed alkali metal ions.
[0064] The positive electrode active material includes a lithium transition metal oxide containing nickel and other transition metals. In the lithium transition metal oxide including nickel and other transition metals, the amount of nickel relative to the total molar number of the transition metal may be 60 mol% or more, for example, 75 mol% or more, for example, 80 mol% or more, for example, 85 mol% or more, or for example, 90 mol% or more.
[0065] For example, the lithium transition metal oxide may be a compound represented by the following formula α: Formula α: Li a Ni x Co y M z O 2-b A b , Wherein, in formula α, 0.9≤a≤1.2, 0≤b≤0.2, 0.6≤x<1, 0<y≤0.3, 0<z≤0.3, and x+y+z=1, M is at least one selected from manganese (Mn), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al) or boron (B), and A is F, S, Cl, Br or a combination thereof. For example, the above subscripts may be 0.7≤x<1, 0<y≤0.3, and 0<z≤0.3; 0.8≤x<1, 0<y≤0.3, and 0<z≤0.3; 0.8≤x<1, 0<y≤0.2, and 0<z≤0.2; 0.83≤x<0.97, 0<y≤0.15, and 0<z≤0.15; or 0.85≤x<0.95, 0<y≤0.1, and 0<z≤0.1.
[0066] For example, the lithium transition metal oxide may be at least one compound represented by the following formula β or formula γ: Formula β: LiNi x Co y Mn z O2, Wherein, in formula β, 0.6≤x≤0.95, 0<y≤0.2, and 0<z≤0.1, for example, 0.7≤x≤0.95, 0<y≤0.3, and 0<z≤0.3.
[0067] Formula γ: LiNi x Co y Al z O2, Wherein, in formula γ, 0.6≤x≤0.95, 0<y≤0.2, and 0<z≤0.1, for example, 0.7≤x≤0.95, 0<y≤0.3, and 0<z≤0.3, for example, 0.8≤x≤0.95, 0<y≤0.3, and 0<z≤0.3, for example, 0.82≤x≤0.95, 0<y≤0.15, and 0<z≤0.15, for example, 0.85≤x≤0.95, 0<y≤0.1, and 0<z≤0.1.
[0068] For example, the lithium transition metal oxide may be LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.88 Co 0.08 Mn 0.04 O2、LiNi 0.8 Co 0.15 Mn 0.05 O2、LiNi 0.8 Co 0.1 Mn0.1 O2、LiNi 0.88 Co 0.1 Mn 0.02 O2、LiNi 0.8 Co 0.15 Al 0.05 O2 or LiNi 0.88 Co 0.1 Al 0.02 O2.
[0069] According to another embodiment, the positive electrode active material includes at least one active material selected from the group consisting of Li-Ni-Co-Al (NCA), Li-Ni-Co-Mn (NCM), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2) and lithium iron phosphate (LiFePO4).
[0070] In some embodiments, the positive electrode material layer includes a positive electrode conductive material; the type of the positive electrode conductive material is not limited, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.
[0071] There is no particular restriction on the type of positive electrode binder used in the manufacture of the positive electrode material layer. In the case of a coating method, any material that can be dissolved or dispersed in the liquid medium used in the manufacture of the electrode can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or their hydrogenates, ethylene-propylene-diene terpolymers (EPDM), Thermoplastic elastomer polymers such as styrene·ethylene·butadiene·ethylene copolymers, styrene·isoprene·styrene block copolymers or their hydrogenated products; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene·vinyl acetate copolymers, propylene·α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene·ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc. The above positive electrode binders can be used alone or in any combination.
[0072] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0073] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, the thickener and styrene-butadiene rubber (SBR) emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.
[0074] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0075] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.
[0076] The positive electrode can be made by forming a positive electrode material layer containing a positive electrode active material and a binder on a current collector. The manufacture of a positive electrode using a positive electrode active material can be carried out by a conventional method, that is, the positive electrode active material and the binder, as well as the conductive material and the thickener as required, are dry-mixed to form a sheet, and the obtained sheet is pressed onto the positive electrode current collector; or these materials are dissolved or dispersed in a liquid medium to form a slurry, and the slurry is applied to the positive electrode current collector and dried to form a positive electrode material layer on the current collector, thereby obtaining a positive electrode.
[0077] Isolation film In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually used by infiltrating the separator.
[0078] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.
[0079] The separator may also be a material formed by laminating the above materials, examples of which include, but are not limited to, a three-layer separator formed by laminating polypropylene, polyethylene, and polypropylene in this order.
[0080] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (eg, barium sulfate, calcium sulfate, etc.). The form of the inorganic material may include, but is not limited to, granular or fibrous.
[0081] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators can also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with alumina particles having a particle size of 90% less than 1 μm.
[0082] The thickness of the separator is arbitrary. In some embodiments, the thickness of the separator is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the separator is within the above range, insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.
[0083] The present application further provides an electronic device, which includes the secondary battery according to the present application.
[0084] The purpose of the secondary battery of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the secondary battery of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0085] Example Below, taking lithium-ion batteries as an example, examples and comparative examples are given to explain the implementation of the secondary battery of the present application in more detail. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are mass references.
[0086] Test Method Safety performance after cycling (thermal shock test) (1) At 25℃±1℃, charge the lithium-ion battery at a constant current of 1.0C to 4.45V, then charge at a constant voltage of 4.45V until the current drops to 0.05C, and then discharge the lithium-ion battery at a constant current of 1.0C to 3.0V before stopping. This is considered a charge and discharge cycle. Perform 200 charge and discharge cycles on the lithium-ion battery.
[0087] (2) At 25℃±1℃, charge the lithium-ion battery at a constant current of 0.5C to 4.45V, then charge at a constant voltage of 4.45V to a current of 0.025C, and then place the lithium-ion battery vertically in a box and heat it up at a rate of 5℃ / min to a specific temperature T (T=100℃) and maintain it for 100 minutes. If the lithium-ion battery does not catch fire or explode within 100 minutes, it is considered to have passed the test.
[0088] When the lithium-ion battery passes the test, repeat steps (1) and (2). When repeating step (2), increase the specific temperature T by 5°C, and keep other operations unchanged. Repeat the above until the lithium-ion battery fails the test, and record the specific temperature T when it passes the test for the last time as the maximum thermal shock temperature.
[0089] For example, "110°C" means that the lithium-ion battery has passed the test at the specific temperature T=110°C and has failed the test at the specific temperature T=115°C.
[0090] Discharge rate at the end of the cycle (1) At 25℃±1℃, charge the lithium-ion battery at a constant current of 1.0C to 4.45V, then charge at a constant voltage of 4.45V until the current drops to 0.05C, and then discharge the lithium-ion battery at a constant current of 1.0C to 3.0V before stopping. This is considered a charge and discharge cycle. Perform 200 charge and discharge cycles on the lithium-ion battery.
[0091] (2) At 25℃±1℃, charge the battery to 4.45V at 0.5C constant current, charge it to 0.05C constant voltage, let it stand for 5 minutes, and discharge it to 3.0V at 0.2C constant current. Record the 0.2C discharge capacity.
[0092] (3) At 25℃±1℃, charge the battery to 4.45V at 0.5C constant current, charge it to 0.05C constant voltage, let it stand for 5 minutes, and discharge it to 3.0V at 2.0C constant current. Record the 2.0C discharge capacity.
[0093] The discharge rate at the later stage of the cycle = 2.0C discharge capacity / 0.2C discharge capacity × 100%.
[0094] Capacity loss rate at the end of the cycle (1) At 25℃±1℃, charge the lithium-ion battery at a constant current of 0.5C to 4.45V, then charge it at a constant voltage of 4.45V to 0.025C, let it stand for 5 minutes, and then discharge it at a constant current of 0.5C to 3.0V. Record the discharge capacity Q1 of the lithium-ion battery. (2) At 25℃±1℃, charge the lithium-ion battery at a constant current of 1.0C to 4.45V, then charge at a constant voltage of 4.45V until the current drops to 0.05C, then discharge the lithium-ion battery at a constant current of 1.0C to 3.0V and stop, which is a standard charge and discharge cycle. After 100 standard charge and discharge cycles of the lithium-ion battery, charge it at a constant current of 0.5C to 4.45V, then charge it at a constant voltage of 4.45V to 0.025C, let it stand for 5 minutes, then discharge it at a constant current of 0.5C to 3.0V, and record the discharge capacity Q2 of the lithium-ion battery; (3) After 100 standard charge and discharge cycles at 25°C ± 1°C, the lithium-ion battery is charged to 4.45V at a constant current of 0.5C, then charged to 0.025C at a constant voltage of 4.45V, left to stand for 5 minutes, and then discharged to 3.0V at a constant current of 0.5C. The discharge capacity Q3 of the lithium-ion battery is recorded.
[0095] The capacity loss rate in the later stage of the cycle = (Q3-Q2) / (Q2-Q1)×100%.
[0096] Particle size and number of particles (Dµm, N1, N2, N3, R1, R2) The tested battery was disassembled to obtain the negative electrode, which was cut into a size of 1 cm×1 cm. The cut surface of the negative electrode was then polished using argon plasma polishing technology to obtain a negative electrode cross-section sample.
[0097] Observe the negative electrode cross section in the backscattered mode of the scanning electron microscope, and randomly select a 40µm×80µm area to be tested in the negative electrode cross section. Count the cross-sectional area S of the first silicon-carbon particle in the tested area, according to S=π×R 2 The particle size D=2R of the selected silicon-carbon particles is calculated by the formula. Silicon-carbon particles with a particle size D greater than or equal to 5µm and less than or equal to 13µm are the first silicon-carbon particles, silicon-carbon particles with a particle size D greater than or equal to 0.1µm and less than or equal to 2µm are the second silicon-carbon particles, and silicon-carbon particles with a particle size D greater than 2µm and less than 5µm are the third silicon-carbon particles. The number of first silicon-carbon particles is N1, the number of second silicon-carbon particles is N2, and the number of third silicon-carbon particles is N3. The area S' of the circumscribed circle of the cross section of the first silicon-carbon particle is counted, and the circularity = S / S'. Three first silicon-carbon particles are randomly selected within the area to be tested to measure the circularity and calculate the arithmetic mean to obtain the circularity R1 of the first silicon-carbon particles. The test method for the circularity R2 of the second silicon-carbon particles is similar.
[0098] Silicon mass percentage test (C1% and C2%) The negative electrode was cut into a size of 1 cm×1 cm, and then the cut surface of the negative electrode was polished using an argon plasma polishing technique to obtain a negative electrode cross-section sample.
[0099] The negative electrode cross section was observed in the backscattered mode of a scanning electron microscope, and three first silicon-carbon particles and three second silicon-carbon particles were randomly selected from the negative electrode cross section sample. The weight percentage of silicon and carbon in the selected particles was tested by energy dispersive X-ray analysis, and the mass percentage of silicon in each particle was calculated. The arithmetic average of the mass percentage of silicon in the first silicon-carbon particles or the second silicon-carbon particles was calculated, and the mass percentage of silicon was C1% and C2%.
[0100] Elongation test of negative electrode current collector (δ) Disassemble the tested battery to obtain the negative electrode, remove the negative electrode material layer to obtain the negative electrode current collector. Cut the negative electrode current collector into a test sample with a length × width of 200mm × 15mm, and mark the original gauge length L0 on the test sample. At a test temperature of 25℃±1℃, use a universal material testing machine to stretch the negative electrode current collector along the length direction at a stretching rate of 5mm / min. The elongation of the test sample at break is L1mm, and the elongation of the negative electrode current collector δ=L1 / L0×100.
[0101] Example 1-1 <Preparation of negative electrode> (1) Preparation of silicon carbon particles: The first carbon skeleton material with an average particle size of 9.2µm and a circularity of 0.96 was placed in a rotary furnace, heated to 480°C in an argon atmosphere and kept warm for one hour, and then the atmosphere was switched to a mixture of argon and silane (the volume ratio of silane to argon was 2:8), and vapor deposition was performed at a deposition temperature of 480°C for 6.5 hours to obtain the first silicon-carbon particles.
[0102] A second carbon skeleton material with an average particle size of 1.1µm and a circularity of 0.78 was placed in a rotary furnace, heated to 480°C in an argon atmosphere and kept warm for one hour. The atmosphere was then switched to a mixture of argon and silane (the volume ratio of silane to argon was 2:8), and vapor deposition was performed at a deposition temperature of 530°C for 4 hours to obtain second silicon-carbon particles.
[0103] A carbon layer is formed on the surface of the first silicon-carbon particle and the second silicon-carbon particle by chemical vapor deposition. The thickness of the carbon layer can be controlled by controlling the time of chemical vapor deposition. The average thickness of the carbon layer on the surface of the first silicon-carbon material is 33 nm, and the average thickness of the carbon layer on the surface of the second silicon-carbon particle is 12 nm.
[0104] (2) Preparation of negative electrode sheet: The first silicon-carbon particles with a carbon layer on the surface, the second silicon-carbon particles with a carbon layer on the surface and artificial graphite are mixed uniformly in a mass ratio of 9.5:0.5:90 as negative electrode active materials. The negative electrode active material, styrene-butadiene rubber, polyacrylic acid, carbon nanotubes and carboxymethyl cellulose are mixed in a mass ratio of 95.8:2.4:0.5:0.5:0.8, and then deionized water is added as a solvent and stirred uniformly to prepare a negative electrode slurry with a solid content of 45wt%. The negative electrode slurry is uniformly coated on one surface of the negative electrode current collector copper foil and dried to obtain a negative electrode sheet coated with a negative electrode material layer on one side. The above steps are repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. After cold pressing, cutting, slitting and drying, a negative electrode sheet is obtained.
[0105] <Preparation of positive electrode> Lithium cobalt oxide, conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. After cold pressing, cutting, slitting, and drying, a positive electrode sheet is obtained.
[0106] <Preparation of Electrolyte> In a dry argon atmosphere glove box, lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solution containing propylene carbonate, ethylene carbonate, ethyl propionate, diethyl carbonate, fluoroethylene carbonate, and vinylene carbonate. Based on the mass of the electrolyte, the mass percentage of LiPF6 was 12.5%, the mass percentage of diethyl carbonate was 10%, the mass percentage of ethyl propionate was 40%, the mass percentage of fluoroethylene carbonate was 12%, and the mass percentage of vinylene carbonate was 0.1%. The remainder was propylene carbonate and ethylene carbonate, and the mass percentage ratio of propylene carbonate to ethylene carbonate was 3:1.
[0107] <Diaphragm> A porous polyethylene film with a thickness of 15 μm was used as the separator.
[0108] <Preparation of lithium-ion batteries> The positive electrode and negative electrode prepared as above are connected to the pole ears respectively. They are stacked via a separator to obtain a laminate. Then, the laminate is housed in an aluminum laminate housing together with an electrolyte. The opening of the housing is heat-sealed, and a lithium-ion battery is prepared through steps such as formation and degassing.
[0109] Examples 1-2 to 1-15, Comparative Example 1 Except for adjusting the parameters according to Table 1, the rest is the same as Example 1-1. The circularity of the porous carbon skeleton is adjusted so that the circularity R1 of the first silicon-carbon particle and the circularity R2 of the second silicon-carbon particle are as shown in Table 1. The temperature of the vapor deposition when preparing the silicon-carbon particles is adjusted so that the silicon element ratio C1 of the first silicon-carbon particle and the silicon element ratio C2 of the second silicon-carbon particle are as shown in Table 1.
[0110] Table 1
[0111] As can be seen from Table 1, the present application regulates the secondary battery negative electrode material layer to include the first silicon-carbon particles and the second silicon-carbon particles, and by controlling the circularity of the first silicon-carbon particles and the second silicon-carbon particles to satisfy R1 / R2>1, it is possible to achieve a higher energy density while taking into account the improvement of the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later stage of the cycle. In particular, on this basis, when the circularity of the two also satisfies 0.05≤R1-R2≤0.15, the secondary battery can exhibit stronger safety performance, discharge rate and capacity retention capacity in the later stage of the cycle.
[0112] In particular, when the mass ratio of silicon in the first silicon-carbon particles and the second silicon-carbon particles is adjusted to meet 35≤C1≤55 and / or 45≤C2≤65, the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle can be improved. Preferably, when the mass ratio of silicon is adjusted to meet 1.2≤C2 / C1≤1.7, the safety performance, discharge rate and capacity retention of the secondary battery in the later cycle can be further improved.
[0113] Example 2-1 to Example 2-17 Except for adjusting the parameters according to Table 2, the rest is the same as Example 1-10. When the parameters shown in Table 2 increase compared with Example 1-10, the content of propylene carbonate and ethylene carbonate is correspondingly reduced; when the parameters shown in Table 2 decrease compared with Example 1-10, the content of propylene carbonate and ethylene carbonate is correspondingly increased. The ratio of the mass percentage of propylene carbonate and ethylene carbonate remains unchanged. "\" indicates that the electrolyte does not contain the substance.
[0114] Table 2
[0115] As can be seen from Table 2, when the electrolyte contains diethyl carbonate and ethyl propionate, and the mass percentage of diethyl carbonate and ethyl propionate in the electrolyte is regulated to meet 2.3≤S2 / S1≤6, the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later cycle can be improved. In particular, when 2.8≤S2 / S1≤4.5 is met, the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later cycle can be further improved. Among them, by comparing Examples 1-10 and 2-6, it can be seen that when the mass content of ethyl propionate in the electrolyte is the same, the mass content of diethyl carbonate is regulated so that its relationship with the mass content of ethyl propionate meets the above range, and the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later cycle are significantly improved. This proves that it is not possible to improve the above-mentioned performance of the secondary battery simply by adjusting the mass content of propyl propionate. It is necessary to regulate the content relationship between the two to satisfy 2.3≤S2 / S1≤6. Through the combined action of propyl propionate and diethyl carbonate, the safety performance, discharge rate and capacity retention ability of the secondary battery in the later stage of the cycle can be improved.
[0116] In particular, the electrolyte is controlled to contain fluoroethylene carbonate and vinylene carbonate. When the mass percentage of fluoroethylene carbonate and vinylene carbonate in the electrolyte is regulated to meet 0.5≤A1 / (100×A2)≤1.8, the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later stage of the cycle can be further improved. In particular, when the relationship of 0.7≤A1 / (100×A2)≤1.5 is controlled to meet, the secondary battery can show more excellent safety performance, discharge rate and capacity retention capacity in the later stage of the cycle.
[0117] In particular, the electrolyte is regulated to contain tetramethyltetravinylcyclotetrasiloxane, and its mass percentage in the electrolyte is controlled to be 0.01% to 0.1%, which can further improve the safety performance, discharge rate and capacity retention of the secondary battery in the later stage of the cycle. In particular, the electrolyte is regulated to contain diethyl (cyanomethyl) phosphonate, and its mass percentage in the electrolyte is controlled to be 0.1% to 0.8%, which can further improve the safety performance, discharge rate and capacity retention of the secondary battery in the later stage of the cycle.
[0118] Example 3-1 to Example 3-6 Except for adjusting the parameters according to Table 3, the rest is the same as Example 1-2. The average particle size of the carbon skeleton material is adjusted to make RA as shown in Table 3. The elongation δ of the negative electrode current collector is adjusted to make the elongation δ of the negative electrode current collector as shown in Table 3.
[0119] Table 3
[0120] It can be seen from Table 3 that when the elongation δ% of the negative electrode current collector is regulated to satisfy 3≤δ≤8, the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later cycle can be further improved. In particular, when the elongation δ% of the negative electrode current collector is regulated to satisfy the relationship of 1.3≤RA / δ≤3.6 with the average particle size RA µm of the first silicon-carbon particles, the safety performance, discharge rate and capacity retention capacity of the secondary battery in the later cycle can be further improved.
[0121] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.
Claims
1. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein: The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises silicon carbon particles, and the particle size of the silicon carbon particles is D μm; The silicon-carbon particles include first silicon-carbon particles and second silicon-carbon particles; when 5≤D≤13, the silicon-carbon particles are first silicon-carbon particles, and the circularity of the first silicon-carbon particles is R1; when 0.1≤D≤2, the silicon-carbon particles are second silicon-carbon particles, and the circularity of the second silicon-carbon particles is R2; R1 / R2>1; The electrolyte contains diethyl carbonate and ethyl propionate. Based on the mass of the electrolyte, the mass percentage of the diethyl carbonate is S1%, the mass percentage of the ethyl propionate is S2%, and 2.3≤S2 / S1≤6. 2 . The secondary battery according to claim 1 , wherein 0.05≤R1-R2≤0.
15.
3. The secondary battery according to claim 1, which satisfies at least one of the following: (1) The first silicon-carbon particles contain silicon and carbon, and based on the sum of the mass of the silicon and carbon elements in the first silicon-carbon particles, the mass proportion of the silicon element is C1%, 35≤C1≤55; and / or, (2) The second silicon-carbon particles contain silicon and carbon. Based on the sum of the mass of the silicon and carbon elements in the second silicon-carbon particles, the mass proportion of the silicon is C2%, and 45≤C2≤65. The secondary battery according to claim 3 , wherein 1.2≤C2 / C1≤1.
7.
5. The secondary battery according to claim 1, wherein the silicon-carbon particles include third silicon-carbon particles; when 2<D<5, the silicon-carbon particles are third silicon-carbon particles; the number of the first silicon-carbon particles is N1, the number of the second silicon-carbon particles is N2, the number of the third silicon-carbon particles is N3, and N3 / (N1+N2+N3)<0.
2. The secondary battery according to claim 1 , wherein 2.8≤S2 / S1≤4.
5.
7. The secondary battery according to claim 1, wherein the electrolyte comprises fluoroethylene carbonate and vinylene carbonate, and based on the mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is A1%, the mass percentage of the vinylene carbonate is A2%, and 0.5≤A1 / (100×A2)≤1.
8. 8 . The secondary battery according to claim 7 , wherein 0.7≤A1 / (100×A2)≤1.
5.
9. The secondary battery according to any one of claims 1 to 8, which satisfies at least one of the following: (1) 0.90≤R1≤0.98; (2) 0.78≤R2≤0.92。 10. The secondary battery according to claim 1 or 6, which satisfies at least one of the following: (1)5≤S1≤20; (2)20≤S2≤45。 11. The secondary battery according to claim 7 or 8, which satisfies at least one of the following: (1)11≤A1≤18; (2)0.05≤A2≤0.5。 12. The secondary battery according to any one of claims 1 to 8, wherein the electrolyte satisfies at least one of the following conditions: (1) The electrolyte contains tetramethyltetravinylcyclotetrasiloxane, and the mass percentage of the tetramethyltetravinylcyclotetrasiloxane is 0.01% to 0.1% based on the mass of the electrolyte; (2) The electrolyte contains diethyl (cyanomethyl)phosphonate, and the mass percentage of the diethyl (cyanomethyl)phosphonate is 0.1% to 0.8% based on the mass of the electrolyte. 13 . The secondary battery according to claim 1 , wherein the elongation of the negative electrode current collector is δ%, and 3≤δ≤8. 14 . The secondary battery according to claim 13 , wherein an average particle size of the first silicon-carbon particles is RA μm, and 1.3≤RA / δ≤3.
6. 15 . The secondary battery according to claim 1 , wherein the silicon-carbon particles comprise a carbon carrier and silicon crystals at least partially distributed inside the carbon carrier. 16 . An electronic device comprising the secondary battery according to claim 1 .
Citation Information
Patent Citations
Carbon material as well as preparation method and application thereof
CN117550586A
Secondary battery
CN118020174A
Secondary battery
CN118104008A
Porous carbon material and preparation method thereof, silicon carbon material, secondary battery and electronic equipment
CN118929651A
Negative electrode material, preparation method therefor and lithium-ion battery
WO2024139392A1